Zeolite and Hucalcia as Coating Material for Improving Quality of NPK Fertilizer in Costal Sandy Soil - Sulakhudin, .; Syukur, Abdul; Sunarminto, Bambang Hendro (JOURNAL OF TROPICAL SOILS, 2011)
The growth and yield of plants are mainly a function of the quantity of fertilizer and water. In coastal sandy soil, nutrient losses and dry soils are seriously problems. The objective of the research was to study effect of zeolite and hucalci concentrations as NPK coating materials on NPK qualities i.e. water adsorption and release of N, P and K. The research used a coastal sandy soil as media. It was conducted in a laboratory of Soil Science Department, Gadjah Mada University from July to August 2009. Experimental design used was a factorial in a completely randomized design. The first factor was hucalci concentration, consisted of 10% (H1), 20% (H2), and 30% (H3). The second factor was zeolite concentration, consisted of 25% (Z1), 50% (Z2), 75% (Z3), and 100% (Z4). NPK fertilizer (without coating) used as a control. The results showed that hucalci and zeolite had a capability to increase water adsorption and to retard the release of N, P, K. The coated NPK with hucalci 30% and zeolite 100% had the highest quality in water absorption, water retention and release of nutrients.Keywords: Coastal sandy soil, humic-calcium, NPK fertilizer, zeolite